2016
DOI: 10.1007/s13277-016-5140-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers for anti-EGFR therapy in metastatic colorectal cancer

Abstract: Anti-epidermal growth factor receptor (EGFR) therapy has established efficacy in metastatic colorectal cancer, but a significant number of patients do not respond to such treatment. Recently, various biomarkers were reported to be useful in predicting resistance to anti-EGFR. All the potential biomarkers predicting resistance to anti-EGFR are reviewed herein from five aspects. First, upstream molecules, including epiregulin (EREG) and amphiregulin (AREG), might play different roles according to their abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…The Combination of cetuximab with chemotherapy is the standard first-line treatment for mCRC patients, especially patients with left-sided mCRC 6 , 7 . Several studies that focused on the MAPK pathway have identified some potential biomarkers with questionable accuracy, but validated predictors of efficacy to cetuximab are still not available 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The Combination of cetuximab with chemotherapy is the standard first-line treatment for mCRC patients, especially patients with left-sided mCRC 6 , 7 . Several studies that focused on the MAPK pathway have identified some potential biomarkers with questionable accuracy, but validated predictors of efficacy to cetuximab are still not available 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of EGFR amplification as prognostic biomarker remains controversial. In two studies in mCRC, authors demonstrated that EGFR amplification was associated with longer PFS and OS [ 31 , 32 ]; otherwise, in another work, EGFR amplification was not associated to prognosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is a transmembrane tyrosine kinase receptor involved in the regulation of cellular multiplication, survival, and differentiation. EGFR is identified as cellular protooncogene and is overexpressed in a variety of human cancers [49]. EGFR inhibitors were used to treat not only non-small-cell lung cancer with EGFR mutation, but also cancer with overexpression of EGFR [50].…”
Section: Discussionmentioning
confidence: 99%